Efektivitas Penggunaan Quizizz terhadap Keaktifan Peserta Didik pada Materi Laju Reaksi di SMAS Adabiah 2 Padang - Hanifah Zahra Arsa; Mawardi (MASALIQ, 2026)
Student engagement is an important factor supporting successful learning, particularly in abstract chemistry topics such as reaction rates. However, learning that remains dominated by lecture methods has resulted in suboptimal student participation and involvement. This study aims to analyze the effectiveness of using Quizizz in enhancing student engagement in reaction rate material at SMAS Adabiah 2 Padang. The study involved 35 Phase F students. Data were collected through a pre-test and post-test and then analyzed using quantitative descriptive techniques supported by qualitative analysis. The findings indicate that the use of Quizizz was effective in increasing student engagement, as reflected in greater participation during learning, involvement in discussions, enthusiasm for taking quizzes, and responses to learning activities. In addition, students’ learning outcomes improved, as indicated by higher post-test scores than pre-test scores. This study concludes that Quizizz can be used as a digital instructional medium to increase student engagement and support learning outcomes in chemistry education. These findings provide practical implications for teachers in developing reaction rate instruction that is more interactive, participatory, and aligned with the characteristics of technology-based learning.